Silver powder composed of three-dimensional granular crystals and two-dimensional flake crystals and preparation method thereof

By reacting in one reaction in the same reaction system to generate silver powder of three-dimensional particle crystals and two-dimensional sheet crystals, the problems of complex and insufficient performance of the existing silver powder mixing process are solved, and high-purity and high-performance silver paste are achieved, suitable for precision printing and high-conductive applications.

CN114743717BActive Publication Date: 2025-05-02PEKING UNIV SHENZHEN GRADUATE SCHOOL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210399670.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-15
Publication Date
2025-05-02
Estimated Expiration
2042-04-15

AI Technical Summary

Technical Problem

The existing silver powder mixing processes of different forms have problems such as complex process, introduction of impurities, and large differences in surface states, which leads to the failure of silver paste performance to meet the requirements of precision printing and high conductivity.

Method used

The silver powder composed of three-dimensional particle crystals and two-dimensional sheet crystals generated in one reaction in the same reaction system is used to control the silver ion concentration, reaction temperature and reducing agent ratio to ensure that the three-dimensional particle crystals account for at least 60% of the total weight and the two-dimensional sheet crystals do not exceed 40%.

Benefits of technology

It realizes the high purity and good printing performance of silver powder. It has the advantages of high strength and good conductivity after sintering. It is suitable for precision printing and high-performance capacitors and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114743717B_ABST
    Figure CN114743717B_ABST
Patent Text Reader

Abstract

The present application discloses a silver powder composed of three-dimensional granular crystals and two-dimensional lamellar crystals and a preparation method thereof. The silver powder composed of three-dimensional granular crystals and two-dimensional lamellar crystals of the present application, wherein the three-dimensional granular crystals and the two-dimensional lamellar crystals are generated by a single reaction in the same reaction system. The silver powder of the present application, since the three-dimensional granular crystals and the two-dimensional lamellar crystals are generated by a single reaction, have similar surface states, thereby avoiding the insufficient purity of the mixed silver powder caused by the introduction of impurities in the preparation process of silver powders of different forms. The silver paste prepared using the silver powder of the present application can be better suitable for precision printing, and has the advantages of high strength and high conductivity after sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of silver powder, and in particular to a silver powder composed of three-dimensional granular crystals and two-dimensional flaky crystals and a preparation method thereof. Background Art

[0002] Silver paste is made by mixing silver powder, glass powder and organic phase. It is widely used as internal electrodes of capacitors, conductors of circuit substrates, solar cells or display panel substrate circuits. When using silver paste, it is usually printed on the substrate to form a specified pattern; then, it is sintered at high temperature to remove the organic solvent and sinter the silver powder into an integrally formed electrode.

[0003] In order to meet the growing demand for use, conductive pastes are required to better adapt to the precision of printed patterns. Therefore, the silver powder is required to have a narrow particle size distribution, a similar surface state, no phase separation in the paste, and good dispersion in the organic phase.

[0004] To this end, some studies have proposed that different forms of silver powder can be mixed to improve the requirements of high conductivity, densification and high adhesion of silver paste. However, the mixing of different forms of silver powder requires the preparation of different forms of silver powder separately, and then the various forms of silver powder are mixed in proportion; this method not only has high process requirements and requires multiple separate preparations; but also, due to the batch-to-batch differences in the preparation process, the surface states of silver powders of different forms vary greatly. In addition, different forms of silver powder are prepared separately and then mixed, the uniformity is poor, and impurities will be introduced during the preparation and mixing process, affecting the performance of the silver paste.

[0005] In summary, the existing processes and methods for mixing silver powders of different forms have many defects and deficiencies, which make the performance of the prepared silver paste unable to meet expectations. Therefore, how to prepare mixed silver powder with better performance is an urgent problem to be solved. Summary of the invention

[0006] The purpose of the present application is to provide an improved silver powder composed of three-dimensional granular crystals and two-dimensional plate-like crystals and a preparation method thereof.

[0007] This application adopts the following technical solutions:

[0008] One aspect of the present application discloses a silver powder composed of three-dimensional granular crystals and two-dimensional lamellar crystals, wherein the three-dimensional granular crystals and the two-dimensional lamellar crystals are generated by a single reaction in the same reaction system.

[0009] It should be noted that in the mixed silver powder of the present application, the three-dimensional granular crystals and the two-dimensional plate-like crystals are generated by a single reaction in the same reaction system, and have similar surface states, thus avoiding the insufficient purity of the mixed silver powder caused by the introduction of impurities in the preparation process of silver powders of different forms. The silver paste prepared by the mixed silver powder of the present application can be better suitable for precision printing, and has the advantages of high strength and high conductivity after sintering.

[0010] In one implementation of the present application, the three-dimensional particle crystals in the silver powder account for at least 60% of the total weight of the silver powder, and the remainder is two-dimensional flake crystals.

[0011] It should be noted that the present application adopts a mixture of at least 60% three-dimensional granular crystals and no more than 40% two-dimensional flake crystals, which can ensure that the silver paste prepared from the silver powder has good printing performance.

[0012] In one implementation of the present application, the size of the three-dimensional particle crystal is 0.3-1.5 μm, and the size of the two-dimensional plate-like crystal is less than 10 μm in length, 5-6 μm in width, and 200-500 nm in thickness.

[0013] Another aspect of the present application discloses a silver paste using the silver powder of the present application.

[0014] It should be noted that the silver paste of the present application has good printing performance due to the use of the silver powder of the present application; and after sintering, it has the advantages of high strength and high conductivity.

[0015] Another aspect of the present application discloses the application of the silver paste of the present application in the internal electrodes of stacked capacitors, LTCC, solar cells, 5G filters, plasma display panels, touch panels, thin film switches based on PET, flexible circuit boards, varistors and thermistors, piezoelectric ceramics or carbon film potentiometers.

[0016] Another aspect of the present application discloses a solar cell silver paste, which is composed of 45-55 parts by weight of the silver powder of the present application, 40-50 parts by weight of an organic phase and 2-7 parts by weight of glass powder.

[0017] It should be noted that the solar cell silver paste of the present application, due to the use of the silver powder of the present application, has better leveling and stability, better printing performance, and can be better suitable for precision printing. It can be understood that the key to the solar cell silver paste of the present application is the use of the silver powder of the present application. As for the organic phase and the glass powder, reference can be made to the existing solar cell silver paste, and no specific limitation is made here.

[0018] Another aspect of the present application discloses a solar cell using the solar cell silver paste of the present application.

[0019] It should be noted that the solar cell of the present application has better product consistency and stability due to the use of the solar cell silver paste of the present application, which solves the problem of decreased printing yield due to poor stability of the silver paste.

[0020] Another aspect of the present application discloses a method for preparing the silver powder of the present application, comprising the following steps:

[0021] controlling the solution of silver ions or silver ion complexes at a reaction temperature;

[0022] Under an inert gas environment, a solution of silver ions or silver ion complexes is stirred, and at the same time, a reducing agent is added thereto for a reduction reaction, and the temperature change is maintained at less than 5° C. during the entire reaction process; and the solvent of the solution of silver ions or silver ion complexes is incompatible with the solvent of the reducing agent;

[0023] After the reduction reaction is completed, a surface coating solution is added to the reaction system for surface coating to obtain a solution containing silver particles;

[0024] The solution containing silver particles is washed with pure water, and after washing, it is dried to obtain dry powder, and the dry powder is crushed to obtain the silver powder of the present application.

[0025] It should be noted that, in the process of reducing silver powder by reducing agent, the solvent of the solution of silver ions or silver ion complexes is made incompatible with the solvent of the reducing agent. When the two are mixed, the two-phase interface is manufactured by using mutually incompatible solvents, thereby producing silver particles of different forms; achieving the simultaneous generation of three-dimensional granular crystals and two-dimensional lamellar crystals in one reaction in one reaction system.

[0026] In one implementation of the application, the source of silver ions is silver nitrate or silver sulfate.

[0027] In one implementation of the application, the silver ion complex is a complex formed by silver ions and at least one of ammonia, ammonium salts, sulfites, sulfates, amines and transition metal ions.

[0028] In one implementation of the application, in the solution of silver ions or silver ion complexes, the solvent is water, and the concentration of silver ions is 0.1-10 mol / L, preferably 0.1-5 mol / L, and more preferably 0.5-2 mol / L.

[0029] It should be noted that if the concentration of silver ions is too high, the silver particles will explode and nucleate, resulting in serious particle agglomeration; if the concentration of silver ions is too low, the economic efficiency will be low and it is not suitable for industrial production.

[0030] In one implementation of the application, the reducing agent is a solution of a substance containing an aldehyde group or a hydroxyl group.

[0031] In one implementation of the application, the substance containing aldehyde groups or hydroxyl groups is at least one of glucose, formaldehyde, acetaldehyde, ascorbic acid, ethylene glycol and glycerol.

[0032] In one implementation of the application, the solvent of the solution of the substance containing aldehyde groups or hydroxyl groups is a solvent that is incompatible with water.

[0033] Preferably, the solvent of the solution of the substance containing an aldehyde group or a hydroxyl group is cyclohexane.

[0034] In one implementation of the application, in the solution of the substance containing aldehyde groups or hydroxyl groups, the concentration of the substance containing aldehyde groups or hydroxyl groups is 10-30%, preferably 15-20%.

[0035] In one implementation of the application, the amount of reducing agent added is 1-10 times the equivalent of the silver ion content, preferably 3-8 times, and more preferably 5-7 times.

[0036] It should be noted that the amount of reducing agent added directly affects the reaction time. If the amount of reducing agent is too small, the reaction time will be too long, while if the amount of reducing agent is too high, the reaction heat will be released instantly, which is not conducive to temperature control.

[0037] In one implementation of the application, the reaction temperature is 5-55°C, preferably 35-50°C, and more preferably 40-45°C.

[0038] It should be noted that the reaction temperature is mainly used to control the progress of the reduction reaction and the size of the primary microcrystals; if the reaction temperature is too low, it is easy to cause the nucleation rate to be too slow, the primary microcrystals to grow, and it is impossible to prepare primary silver microcrystals that meet the requirements, and it is not suitable for printing fine patterns; if the reaction temperature is too high, it is easy to cause the primary microcrystals to be too small and the particle size distribution to be uneven, which is not conducive to the preparation of silver paste.

[0039] It should also be noted that in order to achieve control of the reaction temperature, the temperature rise caused by the reaction heat can be suppressed by lowering the temperature of the reducing solution, controlling the rate of adding the reducing solution, or adding cold water at the same time, or by external circulating water cooling.

[0040] In one implementation of the application, before the reducing agent is added to the solution of silver ions or silver ion complexes, its temperature is controlled to be 3-15°C lower than the solution temperature of silver ions or silver ion complexes, preferably 5-10°C lower than the solution temperature of silver ions or silver ion complexes.

[0041] In one implementation of the application, the surface coating solution is an ethanol solution containing 25-30% oleic acid.

[0042] In one implementation of the application, in order to prevent the agglomeration of silver particles, a dispersant is added to the solution of silver ions or silver ion complexes, or a dispersant is added while stirring and adding a reducing agent.

[0043] In one implementation of the application, the dispersant is at least one of gum arabic, gelatin, PVP, polyethylene glycol, polyacrylic acid, polycarboxylate, poly(meth)acrylic acid derivatives, maleic anhydride copolymers, polyphosphates, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.

[0044] In one implementation of the application, the dispersant is PVP.

[0045] Preferably, the molecular weight of PVP is between 3000-100000, preferably 3000-10000, more preferably 5000-8000.

[0046] The beneficial effects of this application are:

[0047] The silver powder of the present application, because the three-dimensional granular crystals and the two-dimensional plate-like crystals are generated by a single reaction, have similar surface states, thus avoiding the insufficient purity of the mixed silver powder caused by the introduction of impurities in the preparation process of silver powders of different forms. The silver paste prepared by the silver powder of the present application can be better suitable for precision printing, and has the advantages of high strength and high conductivity after sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is a SEM image of the silver powder prepared in the examples of the present application;

[0049] Figure 2 is a SEM image of another silver powder prepared in an example of the present application;

[0050] Figure 3 is a SEM image of the silver powder used as a comparative test in the examples of the present application;

[0051] Figure 4 This is a SEM image of another silver powder used as a comparative test in the examples of this application. DETAILED DESCRIPTION

[0052] At present, the preparation of mixed silver powders of different forms, such as the preparation of mixed silver powders of spherical silver powder and flaky silver powder, usually involves preparing spherical silver powder and flaky silver powder separately, then mixing the two and ball milling them into mixed silver powder. The whole process is complicated and easily introduces impurities; because the spherical silver powder and flaky silver powder are prepared by different methods, the surface states of the two are very different, which affects the performance of the silver paste.

[0053] The present application has found that in the process of preparing silver powder by reducing silver ions with a reducing agent, if the solvent of the reducing agent and the solvent of the silver ions are incompatible, the two-phase interface can be created by using mutually incompatible solvents, so that three-dimensional granular crystals and two-dimensional plate-like crystals can be simultaneously generated in one reaction system to obtain mixed silver powders of different forms. Since they are generated simultaneously in one reaction system, the surface states of the three-dimensional granular crystals and two-dimensional plate-like crystals of the present application are close, and the introduction of impurities by separate generation and mixing is avoided, thereby improving the performance of the silver paste.

[0054] The present application is further described in detail below through specific examples and drawings. The following examples are only used to further illustrate the present application and should not be construed as limiting the present application.

[0055] Example 1

[0056] Dissolve 685g of silver nitrate in 8654g of distilled water, add 84g of potassium phosphate after dissolution, then add 37g of PVPk30, stir evenly to obtain a silver ion complex solution, pour the prepared solution into a double-layer glass beaker, and pass 35°C water into the interlayer of the beaker to keep it warm.

[0057] Under the conditions of stirring at 2000r / min and passing argon gas at 1L / min, a cyclohexane solution of glucose with a mass fraction of 25% is used as the reducing solution, and a reducing solution with a silver ion content of 4 times the equivalent is added to the above solution at a rate of 1 equivalent / min, keeping the temperature change less than 5°C during the process.

[0058] After the addition was completed, the mixture was stirred for 10 minutes, and then 20 g of an ethanol solution containing 30% oleic acid was added for surface coating to obtain a solution containing silver particles.

[0059] The slurry was washed with pure water until the conductivity of the precipitated solution was greater than 0.2 ms, centrifuged, and then placed in an oven and dried at 50° C. for 24 hours to obtain a dry powder, which was then crushed to obtain the silver powder of this example.

[0060] The silver powder in this example was observed using SEM, and the results are as follows: Figure 1 shown. Figure 1 The results show that the silver powder of this example contains both three-dimensional granular crystals and two-dimensional lamellar crystals, and the proportion of the three-dimensional granular crystals is about 95%, and the proportion of the two-dimensional lamellar crystals is about 5%.

[0061] Example 2

[0062] Dissolve 352g of silver nitrate in 3514g of distilled water, add 152g of sodium phosphate after dissolution, then add 23g of gelatin, stir evenly to obtain a silver ion complex solution, pour the prepared solution into a double-layer glass beaker, and pass 40°C water into the interlayer of the beaker to keep it warm.

[0063] Under the conditions of stirring at 3000 r / min and passing argon at 1.3 L / min, a cyclohexane solution of acetaldehyde containing 10% by mass of ethyl acetate was used as a reducing solution, and 1.7 g of ethyl acetate and a reducing solution with 4 times the equivalent of silver ions were added to the above solution at a rate of 1 equivalent / min, keeping the temperature change less than 5°C during the process.

[0064] After the addition was completed, the mixture was stirred for 10 minutes, and then 10 g of an ethanol solution containing 25% oleic acid was added for surface coating to obtain a solution containing silver particles.

[0065] The slurry was washed with pure water until the conductivity of the precipitated solution was greater than 0.2 ms, centrifuged, and then placed in an oven and dried at 50° C. for 24 hours to obtain a dry powder, which was then crushed to obtain the silver powder of this example.

[0066] The silver powder in this example was observed using SEM, and the results are as follows: Figure 2 shown. Figure 2 The results show that the silver powder of this example contains both three-dimensional granular crystals and two-dimensional lamellar crystals, and the proportion of the three-dimensional granular crystals is about 70%, and the proportion of the two-dimensional lamellar crystals is about 30%.

[0067] Comparative test

[0068] For comparison, this example conducted SEM observations on commercially available silver powders. The results are as follows: Figure 3 and Figure 4 shown. Figure 3 This is the SEM image of the imported silver powder DOWA-4A8F. Figure 4 This is the SEM image of domestic silver powder S334 produced by China Shipbuilding Industry Corporation Huanggang Precious Metals Co., Ltd. Figure 3 and Figure 4 The results showed that both the imported silver powder DOWA-4A8F and the domestic silver powder were composed of three-dimensional granular crystals, and no mixture of three-dimensional granular crystals and two-dimensional flake crystals was found.

[0069] Example 3

[0070] On the basis of the above examples 1 and 2, this example further tests the effect of silver ion concentration on the reaction and silver powder. The results show that the particle size distribution of the silver powder can be adjusted by adjusting the silver ion concentration. Generally, the concentration of silver ions needs to be controlled at 0.1-10 mol / L, and the preferred concentration is 0.1-5 mol / L or 0.5-2 mol / L. At this concentration, in combination with other conditions, a mixed silver powder with a three-dimensional particle crystal size of 0.3-1.5 μm and a two-dimensional plate crystal size of less than 10 μm in length, 5-6 μm in width, and 200-500 nm in thickness can be prepared.

[0071] This example further tests different reducing agents. The results show that the reducing agent can be a solution of a substance containing an aldehyde group or a hydroxyl group, such as a cyclohexane solution of glucose, formaldehyde, acetaldehyde, ascorbic acid, ethylene glycol or glycerol.

[0072] In this example, the reaction temperature was further tested on the basis of Example 1. The results showed that the silver powder meeting the requirements could be prepared at a reaction temperature of 5-55°C; the preferred reaction temperature was 35-50°C, and more preferably 40-45°C.

[0073] This example further tests different dispersants based on Example 1. The results show that the dispersant can be gum arabic, gelatin, PVP, polyethylene glycol, polyacrylic acid, polycarboxylate, poly(meth)acrylic acid derivatives, maleic anhydride copolymer, polyphosphate, sodium pyrophosphate, sodium tripolyphosphate or sodium hexametaphosphate; among them, PVP with a molecular weight of 3000-100000 is preferred, PVP with a molecular weight of 3000-10000 is more preferred, and PVP with a molecular weight of 5000-8000 is more preferred.

[0074] In general, no matter what silver ion concentration, reducing agent or dispersant is used, as long as the solvent of the silver ion is water and the solvent of the reducing agent is a solvent that is incompatible with water, such as cyclohexane, silver powder containing both three-dimensional particle crystals and two-dimensional flake crystals can be generated. Moreover, the more water and the less cyclohexane in the two solvents, the greater the proportion of three-dimensional particles in the generated silver powder; that is, for the same amount of reducing substance, the lower the concentration and the more cyclohexane, the greater the proportion of two-dimensional flake crystals in the generated silver powder. As for the silver ion concentration, reaction temperature, reducing agent dosage, dispersant usage, etc., they will only affect the size of three-dimensional particle crystals and two-dimensional flake crystals.

[0075] Applications of silver powder, for example:

[0076] 1. The silver powder, organic phase and glass powder of Example 1 were mixed in a mass ratio of 5:4:0.5 to prepare a silver paste. The silver paste was printed on the back of the solar cell and sintered to form a back silver electrode. A tensile test was performed, and the results showed that it could withstand a tensile force of 3.9N, meeting the use requirements.

[0077] 2. The silver powder, organic phase and glass powder of Example 2 were mixed in a mass ratio of 5:4:0.5 to prepare a silver paste. The silver paste was printed on the back of the solar cell and sintered to form a back silver electrode. A tensile test was performed, and the results showed that it could withstand a tensile force of 4.7N, meeting the use requirements.

[0078] In the above test, the formula of the organic phase is: 5 parts by weight of ethyl cellulose, 5 parts by weight of hydrogenated castor oil, 20 parts by weight of alcohol ester, and 70 parts by weight of diethylene glycol butyl ether acetate. Glass powder: ZnO, SiO2, Bi2O3, Sb2O3, Al2O3, and B2O3 are mixed in a mass ratio of 50:5:30:2:2:11, placed in a muffle furnace at 1100°C for 1 hour, and then poured into water to obtain glass fragments, which are ground into 3μm powder with alcohol, i.e., the glass powder in this example.

[0079] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application, which should be deemed to fall within the scope of protection of the present application.

Claims

1. A method for preparing silver powder, characterized in that: The silver powder is composed of three-dimensional particle crystals and two-dimensional plate-like crystals, and the three-dimensional particle crystals and the two-dimensional plate-like crystals are generated by a single reaction in the same reaction system. The preparation method comprises the following steps: controlling the solution of silver ions or silver ion complexes at a reaction temperature; In an inert gas environment, a solution of silver ions or silver ion complexes is stirred, and at the same time, a reducing agent is added thereto for a reduction reaction, and the temperature change is kept less than 5° C. during the entire reaction process; and the solvent of the solution of the silver ions or the silver ion complexes is incompatible with the solvent of the reducing agent; the solvent of the solution of the silver ions or the silver ion complexes is water; After the reduction reaction is completed, a surface coating solution is added to the reaction system for surface coating to obtain a solution containing silver particles; The obtained solution containing silver particles is washed with pure water, and after washing, it is dried to obtain dry powder, and the dry powder is crushed to obtain the silver powder.

2. The preparation method according to claim 1, characterized in that: The silver ion source is silver nitrate or silver sulfate.

3. The preparation method according to claim 1, characterized in that: The silver ion complex is a complex formed by silver ions and at least one of ammonia water, ammonium salt and amine.

4. The preparation method according to claim 1, characterized in that: In the solution of silver ions or silver ion complexes, the solvent is water, and the concentration of silver ions is 0.1-10 mol / L.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The reducing agent is a solution of a substance containing an aldehyde group or a hydroxyl group.

6. The preparation method according to claim 5, characterized in that: The substance containing aldehyde groups or hydroxyl groups is at least one of glucose, formaldehyde, acetaldehyde, ascorbic acid, ethylene glycol and glycerol.

7. The preparation method according to claim 6, characterized in that: The solvent of the solution of the substance containing aldehyde groups or hydroxyl groups is a solvent that is incompatible with water.

8. The preparation method according to claim 7, characterized in that: The solvent of the solution of the substance containing aldehyde groups or hydroxyl groups is cyclohexane.

9. The preparation method according to claim 7, characterized in that: In the solution of the substance containing aldehyde groups or hydroxyl groups, the concentration of the substance containing aldehyde groups or hydroxyl groups is 10-30%.

10. The preparation method according to claim 9, characterized in that: In the solution of the substance containing aldehyde groups or hydroxyl groups, the concentration of the substance containing aldehyde groups or hydroxyl groups is 15-20%.

11. The preparation method according to claim 5, characterized in that: The amount of the reducing agent added is 1-10 times the equivalent of the silver ion content.

12. The preparation method according to claim 11, characterized in that: The amount of the reducing agent added is 3-8 times the equivalent of the silver ion content.

13. The preparation method according to claim 12, characterized in that: The amount of the reducing agent added is 5-7 times the equivalent of the silver ion content.

14. The preparation method according to claim 5, characterized in that: The reaction temperature is 5-55°C.

15. The preparation method according to claim 14, characterized in that: The reaction temperature is 35-50°C.

16. The preparation method according to claim 15, characterized in that: The reaction temperature is 40-45°C.

17. The preparation method according to claim 5, characterized in that: Before the reducing agent is added to the solution of silver ions or silver ion complexes, its temperature is controlled to be 3-15° C. lower than the solution temperature of silver ions or silver ion complexes.

18. The preparation method according to claim 17, characterized in that: Before the reducing agent is added to the solution of silver ions or silver ion complexes, its temperature is controlled to be 5-10° C. lower than the solution temperature of silver ions or silver ion complexes.

19. The preparation method according to claim 5, characterized in that: The surface coating solution is an ethanol solution containing 25-30% oleic acid.

20. The preparation method according to claim 5, characterized in that: The preparation method further comprises adding a dispersant to the solution of silver ions or silver ion complexes, or adding the dispersant while stirring and adding the reducing agent.

21. The preparation method according to claim 20, characterized in that: The dispersant is at least one of gum arabic, gelatin, PVP, polyethylene glycol, polyacrylic acid, polycarboxylate, poly(meth)acrylic acid derivative, maleic anhydride copolymer, polyphosphate, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.

22. The preparation method according to claim 21, characterized in that: The dispersant is PVP.

23. The preparation method according to claim 22, characterized in that: The molecular weight of PVP is between 3000-100000.

24. The preparation method according to claim 23, characterized in that: The molecular weight of PVP is between 3000-10000.

25. The preparation method according to claim 24, characterized in that: The molecular weight of PVP is between 5000-8000.

26. Silver powder prepared by the preparation method according to any one of claims 1 to 25.

27. The silver powder according to claim 26, characterized in that: The three-dimensional particle crystals in the silver powder account for at least 60% of the total weight of the silver powder, and the remainder is two-dimensional plate-like crystals.

28. The silver powder according to claim 26 or 27, characterized in that: The size of the three-dimensional particle crystal is 0.3-1.5 μm, and the size of the two-dimensional plate-like crystal is less than 10 μm in length, 5-6 μm in width, and 200-500 nm in thickness.

29. A silver paste using the silver powder according to any one of claims 26 to 28.

30. Application of the silver paste according to claim 29 in internal electrodes of stacked capacitors, LTCC, solar cells, 5G filters, plasma display panels, touch panels, thin film switches based on PET, flexible circuit boards, varistors and thermistors, piezoelectric ceramics or carbon film potentiometers.

31. A solar cell silver paste, characterized in that: The method comprises 45-55 parts by weight of the silver powder according to any one of claims 26 to 28, 40-50 parts by weight of an organic phase and 2-7 parts by weight of glass powder.

32. A solar cell using the solar cell silver paste according to claim 31.

Citation Information

Patent Citations

  • Silver powder and silver paste for back electrode of solar cell and solar cell

    CN104668572A

  • Composite silver powders with silver wires and a preparation method and application thereof

    CN110899721A

  • Silver micro powder and preparation method and application thereof

    CN114054769A